William Gibson's Archangel - Gibson, William, 1948-; Smith, Michael St. John (IDW Publishing, 2017)
"The U.S. political leaders of 2016 abandon the radioactive planet they've destroyed and harness the power of humanity's last hope: The Splitter, a colossal machaine designed to manufacture a bright new reality for them to infiltrate and corrupt."--Page [4] of cover.